TELAAH TERHADAP FIKIH ZAKAT KONVENSIONAL (Upaya Rekonstruksi Fikih Zakat Agar Lebih Fungsional dan Berdaya Guna) - Zainuddin Abdillah (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2018)
Zakat is one of the five pillars of Islam. Zakat potential is extraordinary in Indonesia and it is still not used maximally. It happens because there are still obstacles, either traditional attitudes of people in managing zakat or the institution of government (BAZNAS) is still not effective. For that, in order to be more functional and useful, we need new innovations either in the management system, human resources or the concept of zakat follows new condition. And also, the roles of government need to be more concrete than only making regulation. Therefore, the government has to have power to force.